A study of the Roman Catholic Church in Malaysia / Tan Po Wen - Tan, Po Wen (1984)
Roman Catholicism had come to Malaysia since 1511 with the advent of the Portuguese missionaries. Despite wars with the Muslims or the Dutch and English trader over the years, Roman Catholicism had managed to prevail and establish themselves it is this country. Throughout the years, the number of Catholic in Malaysia have increased tremendously and the training of indigenous priests is made possible locally. The Roman Catholics mission is to spread the gospel, the truth about Christian salvation and to convert tho local residents to Catholics. In the early seventies, the Roman Catholic joined the World Council or Churches and delivered new decrees concerning their religion. These decrees stress the importance of ecumenism which presents the faith with an attitude of love and respect for other religions, and enculturing themselves with certain elements from other religions and cultures so as to enable the locals to identify themselves with Catholicism. Active Christian committees are also stressed upon to spread their faith more effectively. Hence, the Roman Catholic churches which are situated throughout the 4 diocese and archdiocese in Malaysia are building active Christian communities which help in combating the socioeconomic problems of the nation and practising ecumenism through dialogues with other religions so as to better understanding them. Hence, with a strong historical background to support them, the Roman Catholic Church in Malaysia hopes to spread their faith more effectively through their activities and communities.